Dental status of children with congenital defects of the heart and main vessels in Ukraine - Vovchenko Л. О.; Zhachko Н. І. (Actual Dentistry, 2024)
Introduction: Congenital heart disease (CHD) is one of the most common congenital defect worldwide. The increase in the number of patients with CHD creates a group of people with individual special care needs, including dental care. Purpose: to evaluate oral health conditions (oral hygiene, caries experience, periodontal health) in children with CHD and compare their caries experience with the one of the group of healthy children in Ukraine. Materials and methods: Fifty-eight children with congenital heart disease and eighty healthy children aged 3-15 years were enrolled in this study. According to their age and period of dentition, all the children were subdivided into 3 groups: with primary, mixed and permanent dentition. Caries experience, oral hygiene, periodontal health and dental developmental defects were assessed. A one-sample Kolmogorov-Smirnov test and an independent measures t-Test were used. All statistical analyses were performed using the statistical software (SPSS version 26.0, SPSS Inc.). The statistical significance was set at 5%. Results and discussion: The caries experience of children with CHD and healthy children in primary dentition was 4.0 and 6.4 respectively. The highest DMFT was registered in children with CHD in mixed (4.7) and permanent (4.6) dentitions. 33,3% of children with primary dentition and up to 52,9% in mixed dentition had poor oral hygiene. Conclusions: According to limitation of this epidemiological study, there were no significant differences in caries experience of children with congenital heart disease and healthy children in primary and mixed dentitions. These findings indicate the importance of preventive dental care and appropriate treatment of children with CHD.